Expressions textuelles, performatives et filmiques des manifestes féministes – pratiques multiples dans les années 1970 et 2000 - Muriel Andrin (Itinéraires)
This paper, in addition to filling the gap left by the anthologies, aims to highlight the reappropriation of the manifesto through specific mediums by feminist artists in the 1970s and in the 2000s. As they enlarge the definition of the manifesto through practices that go beyond the text or extend it, feminist artists raise the question of a possible filmwriting (cinécriture), as Agnès Varda calls it, a new form of cinematic language always unique that applies to all levels of production of the work, and fully achieve Danchev’s sentence: “to manifesto is to perform.” The manifesto appears to be at once a programmatic, political and symbolic discourse of feminist positioning.